Enhancing Digital Literacy Through Instructional Videos and Social Media Engagement - Rizka Estisia Pratiwi; Mochamad Malik Akbar Rohandi; Rezi Muhamad Taufik Permana; Nadia Meirani (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Digital literacy is an important factor in supporting the implementation of more optimal learning activities in Early Childhood Education (PAUD), more than that digital literacy can have a good influence on the development of early childhood. The purpose of this research is to provide a further understanding of digital literacy and social media interactions in the PAUD Education environment. As well as providing complete counseling on techniques and materials for making interactive learning videos. This service program uses participatory techniques through mentoring and training methods with comprehensive teaching media based on learning videos to meet learning needs in PAUD. Teachers will be given training on various digital applications that can support learning. Teachers and parents will have the ability to make teaching videos for students and children, which will indirectly direct them to become content creators in the field of education.